Characterization method for surface stability of positive electrode material
Through the reaction of lithium cobalt oxide positive electrode material with buffer solution and photoelectrode-assisted titration detection, the accuracy and rapidity of surface stability characterization of lithium-ion battery positive electrode materials are solved, and effective evaluation of cycle life and material screening are achieved.
Patent Information
- Application Number
- CN202311632693.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-30
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art is difficult to quickly and accurately characterize the surface stability of the cathode material of lithium-ion batteries, especially in simulated battery chemistry environments, resulting in limitations in cycle life prediction.
The lithium cobalt oxide positive electrode material was used to react with buffer solution, and the dissolution metal concentration was detected through solid-liquid separation, EDTA complexation and photometric electrode-assisted titration, and calculated and converted into Co[ppm] to evaluate the cycle life of the material. The method uses buffer solutions to simulate the battery chemistry environment, controls the corrosion reaction rate, and improves test accuracy through retitration design and indicator chromogenic reaction.
It realizes rapid and accurate detection of the surface stability properties of different lithium cobalt oxide positive electrode materials, can predict their cycle life, and is suitable for the production quality control of various positive electrode materials, reducing the complexity of data analysis.
Smart Images

Figure CN119224205A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium ion battery electrode materials, and in particular to a method for characterizing the surface stability of positive electrode materials. Background Art
[0002] Since its commercialization, lithium-ion batteries have become the world's most important portable mobile power and energy storage batteries due to their outstanding advantages such as high energy density, no memory effect, and long life. They are widely used in mobile phones, notebooks, smart watches, Bluetooth headsets, drones, and new energy vehicles. Now with the commercialization of 5G and the explosion of new energy vehicles, lithium-ion battery technology is iterating and innovating, and market demand is growing rapidly. Lithium-ion battery energy storage technology has become the core of competition in the energy storage industry market, and research on new lithium-ion batteries has become a technical hotspot for major manufacturers to compete.
[0003] The structure of lithium-ion battery mainly includes positive electrode, separator, negative electrode and electrolyte. + The storage and release of electrical energy is achieved through the embedding and extraction reactions between the positive and negative electrodes. After the lithium-ion positive electrode material is made into a battery, trace amounts of HF in the electrolyte will corrode the positive electrode material, dissolve transition metal ions and coating material substances, destroy the surface integrity of the positive electrode material, and lead to a decrease in stability; during the use of the battery, especially under high temperature and high voltage and high current discharge conditions, the temperature inside the battery rises, and more Li + Being charged leads to more Co 3+ Oxidation to Co 4+ , increased Co 4+ Opportunity to react with electrolyte, cobalt dissolves in electrolyte; doping and coating methods are usually used to solve the surface stability of the above positive electrode materials. 3+ 、Ti 4+ 、V 5+ , Nb 5+ Cr 3+ 、Si 4+ 、Zr 4+ Plasma can inhibit the dissolution of transition metals, increase the Me-O bond energy, fix the lattice oxygen on the surface of the material, and thus stabilize the surface structure; in terms of coating, metal oxides (such as TiO2, ZrO2, SnO2, La2O3, Al2O3, MgO), fluorides (such as AlF3, MgF2), phosphates (such as Li3PO4, AlPO4, YPO4), fast ion conductors (such as Li2TiO3) and other materials are used to coat the surface of high-voltage positive electrode materials. The surface coating layer can serve as a physical isolation layer to effectively prevent the positive electrode material from directly contacting the electrolyte and play a protective role;
[0004] Among the methods for characterizing the surface stability of materials, the industry often uses an indirect method for characterizing electrical properties, that is, the positive electrode material is doped and coated and then assembled into a battery, and the surface uniformity and stability of the positive electrode material are proved to be improved through the improvement of electrical properties (improvement of cycle performance, improvement of high-temperature storage performance, etc.), but this method requires a certain characterization cycle, and does not characterize its stability from the material itself: In terms of direct characterization methods for material surface stability, CN103411987B discloses a method for characterizing the uniformity of titanium dioxide surface coating, using an X-ray spectrometer to test the difference between the maximum and minimum values of the content of chemical elements in the same coating layer in the chemical composition at different points on the titanium dioxide surface to characterize the surface uniformity of the material. CN112798630A uses cross-sectional energy spectrum scanning to observe the uniformity of the distribution of elements on the surface and in the bulk of the material. As can be seen from the above patents, this kind of local microscopic selective component analysis has certain limitations and selection problems, and cannot accurately reflect the stability of the material in actual use scenarios; CN111380996A discloses a method for dissolving lithium iron phosphate with hydrochloric acid, according to the C in the solution. Fe The patent discloses a method for evaluating the cycle life of the LiFePO4 positive electrode material. The patent characterizes the stability of the positive electrode material from the perspective of battery use, develops the idea of characterizing the stability of the positive electrode material and puts it into practice. Summary of the invention
[0005] The purpose of the present invention is to provide a method for characterizing the stability of positive electrode materials in a simulated battery chemical environment system, which can quickly detect and compare the surface stability properties of different lithium cobalt oxide positive electrode materials, thereby quickly predicting the cycle life of the positive electrode material.
[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is as follows:
[0007] A method for characterizing the surface stability of a positive electrode material comprises the following steps:
[0008] (1) mixing powder of lithium cobalt oxide positive electrode material with a buffer solution to react;
[0009] (2) subjecting the reaction mixture obtained in step (1) to solid-liquid separation to obtain a filtrate and insoluble matter;
[0010] (3) Accurately weigh the filtrate obtained in step (2), add a complexing agent EDTA solution to mix and react, and add an indicator solution to form a test solution;
[0011] (4) titrating the test solution formed in the detection step (3) with a CoSO4 titration solution with the aid of a photometric electrode, calculating the dissolved metal concentration by the following formula, converting the dissolved metal concentration into metal element Co [ppm], and evaluating the cycle life of the lithium cobalt oxide positive electrode material based on the converted metal element Co [ppm];
[0012] Dissolved metal concentration [mMol / L / g] = (0.001 × EDTA solution weight [g] – 0.000612 × VEQ volume [ml]) × buffer solution weight [g] / (lithium cobalt oxide cathode material weight [g] × filtrate weight [g]);
[0013] Converted Co [ppm] = 58.933 × dissolved metal concentration [mMol / L / g] × 1000;
[0014] Wherein, VEQ volume [ml] represents the volume of CoSO4 titration solution used, in ml.
[0015] Furthermore, the lithium cobalt oxide positive electrode material is one of lithium cobalt oxide, NCM (Nickel-Cobalt-Manganese), and NCA (Nickel-Cobalt-Aluminum).
[0016] Furthermore, the buffer solution in step (1) is one of disodium hydrogen phosphate-citric acid buffer, citric acid-sodium hydroxide-hydrochloric acid buffer, acetic acid-sodium acetate buffer, acetic acid-lithium acetate buffer, potassium dihydrogen phosphate-sodium hydroxide buffer, and disodium hydrogen phosphate-potassium dihydrogen phosphate buffer; preferably, acetic acid-lithium acetate buffer is selected, which will not be affected by other metal elements (mainly non-positive electrode material component elements) in the test.
[0017] Furthermore, the lithium cobalt oxide positive electrode material used in step (1) is mixed with the buffer solution in a weight ratio of 1: (5-20), and stirred on a magnetic stirrer at a speed of 200-400 rpm for 20-120 min at a temperature of 20-50° C.; preferably, stirred at 350 rpm for 60 min at 25° C.
[0018] Furthermore, the concentration of the EDTA solution used in step (3) is 0.001M.
[0019] Furthermore, the indicator solution used in step (3) is a xylenol orange indicator solution, which is prepared by dissolving 0.2 g of xylenol orange in 100 mL of a mixed solvent of ethanol and H2O of equal mass.
[0020] Furthermore, in step (3), 200 to 600 μL of xylenol orange indicator solution is added using a pipette; preferably, 500 μL of xylenol orange indicator solution is added to ensure that the titration endpoint E is lower than 40% T (transmittance).
[0021] Furthermore, the photometric electrode used in step (4) is a DP5 photometric electrode equipped with a Mettler Toledo T5 automatic titrator.
[0022] Furthermore, the concentration of the CoSO4 titration solution used in step (4) is 0.000612 M, back titration is adopted, and the amount of titration solution added is cut off when the titration end point E is lower than 40% T, and the value is within the allowable range.
[0023] The present invention has the following advantages:
[0024] 1. The pH value of the electrolyte of the lithium-ion battery is generally between 5.5 and 6.5. The pH value of the buffer solution selected in the present invention is close to or preferably falls within this range. The buffer solution is used to corrode the surface of the positive electrode to characterize the stability of the material, which to a certain extent offsets and reduces the effect of the alkali on the surface of the positive electrode material on the pH value of the solution, thereby maintaining the pH value of the solution relatively stable and making the corrosion reaction rate controllable;
[0025] 2. Adopting the design idea of back titration, EDTA fully complexes with various metal ions (main metal elements of positive electrode materials: Co, Ni, Mn, etc., as well as doped / coated metal elements, such as Al, Ti, Mg, Zr, V, W, La, Y, etc., and impurity elements, such as Cu, Fe, Cr, Pb, etc.), and fully considers the possibility of dissolution of various metals;
[0026] 3. Through the color development reaction of xylenol orange, the photoelectrode is used to confirm the titration endpoint, which improves the accuracy and sensitivity of the test;
[0027] 4. The data processing is converted to Co [ppm], and each dissolved metal is uniformly converted to Co dissolved amount for quantitative expression. The data display is simple and comparable, avoiding direct or indirect comparison of various dissolved metals and reducing the complexity of data analysis;
[0028] 5. The method of the present invention has a wide range of applications and is applicable to various positive electrode materials. It can be used for product design and production quality control. It is a rapid detection method for comparing the stability differences between materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is the graph of titration potential change in the embodiment.
[0030] Figure 2 This is the 4.50V (0.2C) cycle diagram of the full battery with different positive electrode materials in Example 1. DETAILED DESCRIPTION
[0031] In order to make the various technical features and advantages or technical effects in the above technical solutions of the present invention more obvious and easy to understand, they are described in detail below with reference to the accompanying drawings.
[0032] 1. Test methods and material sources: In each embodiment and comparative example, unless otherwise specified, the chemical raw materials used are commercial materials commonly used in the battery industry and analysis field, and the physical and chemical parameters and performance parameters involved are measured using conventional methods in the field. Some specific raw materials and parameter test methods are as follows.
[0033] Preparation of CoSO4 titration solution: Add 0.172g of cobalt (II) sulfate heptahydrate to a beaker, dissolve in ultrapure water, transfer to a 1000ml volumetric flask, make up to volume with ultrapure water, mix well. Transfer to a brown reagent bottle for later use.
[0034] Preparation of buffer solution: Add 0.6 ml of acetic acid and 4.18 g of lithium acetate dihydrate to a 1000 ml volumetric flask. Add ultrapure water to volume and mix well. Transfer to a plastic bottle and seal for later use.
[0035] Preparation of xylenol orange indicator solution: Dissolve 0.2 g of xylenol orange in 100 ml of ethanol:H2O (50:50 wt%) and transfer to a brown bottle for later use.
[0036] 2. Lithium cobalt oxide positive electrode material: LCOI, LCOII, LCOIII, LCOIV and LCOV used in each embodiment are lithium cobalt oxide positive electrode materials produced by Taifeng Xianxing Lithium Energy Technology Co., Ltd., which differ in coating properties and other aspects.
[0037] Embodiment 1:
[0038] (1) Accurately weigh 2.5 g of each LCOI, LCOII, LCOIII, LCOIV and LCOV powder sample to an accuracy of 0.0001 g and add them into 100 ml plastic beakers respectively;
[0039] (2) Place a clean magnetic stir bar, accurately measure five 25g buffer solutions, accurate to 0.0001g, add them to the beakers in step (1), respectively, and start the stirring reaction at room temperature;
[0040] (3) Cover the solution with a polyethylene film and stir at 350 rpm on a magnetic stirring plate for 60 min;
[0041] (4) Using a 50 ml syringe with a 0.2 μm needle filter, extract 100 ml of solution from the beaker and record the weight of the filtrate accurately to 0.0001 g;
[0042] (5) Add 16 g of EDTA solution; record the weight to the nearest 0.0001 g; use a pipette to add 500 μL of indicator solution, and add the above to the extraction solution of step (4) to form a test solution;
[0043] (6) Place the titration cups containing the test solution on the automatic sample injector of the Mettler Toledo T5 automatic titrator in order, fill the burette with CoSO4 titration solution, select 590nm (yellow) light for the DP5 electrode, start automatic titration, and cut off the amount of titrant added when the endpoint E is less than 40% T. Record the volume of CoSO4 solution used VEQ;
[0044] (7) Calculate the converted Co [ppm] according to the formula.
[0045] Embodiment 2:
[0046] The detection process of the five kinds of lithium cobalt oxide powders is the same as that of Example 1, except that in step (4), the filtrate is taken for ICP detection to detect the concentration of dissolved elements (such as Li, Co, Al, Mg, Ti, La, Y, Zr, etc.).
[0047] Embodiment 3:
[0048] The detection process of LCOI powder is the same as that of Example 1, except that the amount of titrant added in step (6) is cut off at the endpoint and the volume of CoSO4 solution used is recorded.
[0049] Comparative Example 1:
[0050] The detection process of LCOI powder is the same as that of Example 1, except that in step (2), 3% HCl solution is added, and in step (4), the filtrate is taken for ICP detection to detect the concentration of dissolved elements (such as Li, Co, Al, Mg, Ti, La, Y, Zr, etc.), and steps 5-7 are omitted.
[0051] Comparative Example 2:
[0052] The detection process of LCOI powder is the same as that of Example (1), except that in step (2), 50% aqua regia solution is added, and in step (4), the filtrate is taken for ICP measurement to detect the concentration of dissolved elements (such as Li, Co, Al, Mg, Ti, La, Y, Zr, etc.), and steps 5-7 are omitted.
[0053] The converted Co[ppm] and ICP test data of each element in the comparative example and the ICP test data of each element in the comparative example, the converted Co[ppm] and electrical performance test of the example test, the results are as follows:
[0054] Table 1 Comparison of ICP test data of LCOI in Example 1 and Comparative Examples 1-2
[0055] Experiment number Sample No. Li / ppm Co / ppm Al / ppm Mg / ppm Ti / ppm La / ppm Y / ppm Zr / ppm Example 1 LCOI 88.2 73.2 0.9 55.3 0 8.2 13.8 0 Comparative Example 1 LCOI 31.1 129.3 1.9 1.2 1.1 1.4 0.9 0.2 Comparative Example 2 LCOI 415.4 1887.3 18.5 4.6 3.5 3.1 1.3 0.3
[0056] From the ICP test data results in Table 1, the ICP detected substances in the embodiment and the comparative example are different. The buffer solution forms a stable pH due to weak acid and salt, and mainly reacts with the coating material (Al, Mg, La, Y). Hydrochloric acid and aqua regia dissolve more Li and Co, indicating that they mainly react with the lithium cobalt oxide body (it can also be understood that the strong pH acidic solution has completely reacted with the coating material elements on the surface of the positive electrode material, and the reaction ratio with the positive electrode material body has increased, resulting in a decrease in the numerical ratio of the coating element). This weakens the focus of the test on the surface properties, and the use of hydrochloric acid and aqua regia loses the significance of characterizing the surface stability of the positive electrode material; this shows that the pH (3.6-5.8) of the acetic acid-lithium acetate buffer solution used in the present invention is close to the pH value (5.5-6.5) of the electrolyte of the lithium ion battery and falls within the range, which can better simulate the chemical reaction state of the positive electrode material in the electrolyte, and the type and amount of dissolved elements can better illustrate the surface stability characteristics of the material.
[0057] Figure 1 It is a titration potential change diagram. The method of the present invention uses a photometric electrode assisted potentiometric titration for back titration. Due to the different surface stability of different materials, the types and amounts of elements dissolved from the surface are different, and the amount of EDTA consumed is different, the amount of indicator added will affect the change of the titration end point. Therefore, it is necessary to adjust the amount of indicator added to control the titration end point E to be less than or equal to 40% T to meet the test accuracy;
[0058] Table 2 Comparison test results of LCOI of Example 1 and Example 3
[0059] Experiment number Sample No. Converted Co[ppm] Example 1 LCOI 88.6 Example 3 LCOI 126.4
[0060] Table 2 is a comparative test result of LCO1 in Example 1 and Example 3. The present invention adopts the preferred fixed endpoint E lower than 40% T as the titration endpoint.
[0061] Table 3 Detection results of different lithium cobalt oxide positive electrodes in Example 1
[0062]
[0063] Table 3 shows the ICP test results and the converted Co [ppm] values of different lithium cobalt oxide positive electrode materials in Example 1. From the ICP data, the types of dissolved metals are different between different materials, and the dissolved values and proportions of different elements are different and irregular. From the perspective of ICP data, it is impossible to uniformly interpret the data and give evaluation results; by converting the value of Co [ppm], a quantitative comparison of a single value can be performed, and it can be found that the present invention solves the problem of uniformity and quantitative comparison of data processing from the beginning of the test mechanism;
[0064] Figure 2It is the intermittent cycle performance of different positive electrode materials at 4.5V of the full battery in Example 1. The energy retention rate of the sample cycle performance obtained from the figure is ranked LCOIV>LCOII>LCOIII>LCOI>LCOV, which is basically consistent with the numerical ranking of the converted Co [ppm] obtained by the test in Example 1. This also verifies from the result that the cycle performance of the battery material is affected by the amount of metal dissolution. The present invention assumes that the material has better surface coating and less metal dissolution. If the material coating is poor, more metal will be dissolved. A buffer solution with a pH close to that of the electrolyte is used to simulate the initial stability of the material in the battery system, and a metal dissolution data law consistent with the full battery cycle law is obtained. The influence of each metal element is combined by back titration, and the converted Co [ppm] is uniformly quantified for numerical comparison, which plays a role in quickly characterizing the stability of lithium-ion battery materials and predicting the full battery cycle performance.
[0065] In summary, the characterization method of the present invention can effectively simulate the stability properties of different positive electrode surfaces in the battery system. The buffer solution reacts chemically with the positive electrode surface, the reaction system is stable and controllable, and back titration is performed with the cooperation of a photometer to comprehensively react to the dissolution of various metal elements. The data is converted into Co [ppm] and the data is quickly compared. The test results of this method correspond to the cycle properties of the entire battery and can be used as a rapid method for screening materials.
[0066] The above contents are further explanations of the present invention in combination with specific optional implementation methods, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or replacements made without departing from the concept of the present invention should be regarded as falling within the scope of protection of the present invention.
Claims
1. A method for characterizing the surface stability of a positive electrode material, characterized in that: The following steps are involved: (1) mixing powder of lithium cobalt oxide positive electrode material with a buffer solution to react; (2) subjecting the reaction mixture obtained in step (1) to solid-liquid separation to obtain a filtrate and insoluble matter; (3) Accurately weigh the filtrate obtained in step (2), add a complexing agent EDTA solution to mix and react, and add an indicator solution to form a test solution; (4) titrating the test solution formed in the detection step (3) with a CoSO4 titration solution with the aid of a photometric electrode, calculating the dissolved metal concentration by the following formula, converting the dissolved metal concentration into metal element Co [ppm], and evaluating the cycle life of the lithium cobalt oxide positive electrode material based on the converted metal element Co [ppm]; Dissolved metal concentration [mMol / L / g] = (0.001 × EDTA solution weight [g] – 0.000612 × VEQ volume [ml]) × buffer solution weight [g] / (lithium cobalt oxide cathode material weight [g] × filtrate weight [g]); Converted Co [ppm] = 58.933 × dissolved metal concentration [mMol / L / g] × 1000; Wherein, VEQ volume [ml] represents the volume of CoSO4 titration solution used, in ml.
2. The characterization method according to claim 1, characterized in that The lithium cobalt oxide positive electrode material is lithium cobalt oxide, NCM, NCA One of them.
3. The characterization method according to claim 1, characterized in that The buffer solution in step (1) is one of disodium hydrogen phosphate-citric acid buffer, citric acid-sodium hydroxide-hydrochloric acid buffer, acetic acid-sodium acetate buffer, acetic acid-lithium acetate buffer, potassium dihydrogen phosphate-sodium hydroxide buffer, and disodium hydrogen phosphate-potassium dihydrogen phosphate buffer.
4. The characterization method according to claim 1, characterized in that The lithium cobalt oxide positive electrode material used in step (1) is mixed with the buffer solution in a weight ratio of 1:(5-20), and stirred on a magnetic stirrer at a speed of 200-400 rpm for 20-120 min at a temperature of 20-50° C.
5. The characterization method according to claim 1, characterized in that The concentration of the EDTA solution used in step (3) is 0.001M.
6. The characterization method according to claim 1, characterized in that The indicator solution used in step (3) is a xylenol orange indicator solution, which is prepared by dissolving 0.2 g of xylenol orange in 100 mL of a mixed solvent of ethanol and H2O of equal mass.
7. The characterization method according to claim 1 or 6, characterized in that: In step (3), add 200-600 μL using a pipette. Xylenol orange indicator solution.
8. The characterization method according to claim 7, characterized in that: In step (3), 500 μL of xylenol orange indicator solution was added using a pipette to ensure that the titration endpoint E was less than 40% T.
9. The characterization method according to claim 1, characterized in that: The photometric electrode used in step (4) is a DP5 photometric electrode equipped with a Mettler Toledo T5 automatic titrator.
10. The characterization method according to claim 1, characterized in that: The concentration of the CoSO4 titration solution used in step (4) is 0.000612M. Back titration is adopted, and the amount of titration solution added is cut off when the titration end point E is lower than 40%T.
Citation Information
Patent Citations
A method for characterizing the uniformity and dispersibility of titanium dioxide surface coating
CN103411987B
A rapid detection method for the cycle life of a positive electrode material
CN111380996A
Preparation method of sample for characterizing element distribution uniformity
CN112798630A
